Peculiar Features of Alternative Assessment in Teaching English as A Foreign Language (Eurasian Research Bulletin, 2022)
In all academic settings, assessment is viewed as closely related to instruction. Assessment is needed to help teachers and administrators make decisions about students’ linguistic abilities, their placement in appropriate levels, and their achievement. The article analyses importance and benefits of alternative assessment in teaching English as a foreign language.